Centenary Tribute: Kodati: Doyen of Library Movement and Public Library Development in Andhra Pradesh - Raju, A. A. N. (Journal of Information and Knowledge, 2014)
Kodati Narayana Rao (1914-2002) popularly known as ’Kodati’ dedicated almost seven decades of his public life for the cause of library movement and public library development in the Telangana region of former Hyderabad State and Coastal Andhra region of former Madras Presidency and later in Andhra Pradesh. From childhood days he showed keen interest in opening of libraries and library movement. He opened new Libraries and assisted in reviving dormant libraries. Very successfully organized Andhra Desa Library Association Annual Conferences in Telangana region in 1940s and helped emotional integration of Telugu people living in Hyderabad State and Coastal Andhra. He closely associated with Andhra Pradesh Library Association and served as its President for nearly four decades. He also served as President of Sri Krishna Devaraya Andhra Bhasha Nilayam (1901) and very successfully organized its Diamond Jubilee Celebrations in 1962. After the enactment of A.P. Public Libraries Act, 1960, Kodati became the first Chairman of Hyderabad City Grandhalaya Samstha in the year 1961 and later Chairman of A. P. Grandhalaya Parishat in the year 1992. He also very closely associated with Gandhi Smarak Nidhi, Cooperative Movement, Khadi Movement, Gandhi Bhavan Trust and Freedom Movement. He was Member of Ekbote Committee (1976) and Vavilala Committee (1978) which were appointed by the Government of Andhra Pradesh to look into the working of A. P. Public libraries’ Act 1960 and state of private libraries in Andhra Pradesh. During his long journey of seven decades of public service, Kodati received many awards including D.Litt. from Kakatiya University, Warangal. He passed away on 19th November 2002 at the ripe age of 88 years.